مواصلات و ابلاغیات میں مؤثر حکم و مصالح: سیرت النبی ﷺ کے تناظر میں نبوی اقدامات کا اطلاقی مطالعہ: Effective Communication and Strategic Messaging: An Applied Study of Prophetic Measures in Light of the Seerah - Hafiz Jamil Khalil; Dr Attiq ur Rahman; Hafiza Ambreen Fatima (AL-IDRAK JOURNAL, 2024)
This study explores the principles of effective communication and strategic messaging in light of the Seerah of the Prophet Muhammad ﷺ. By analyzing the Prophet’s ﷺ approach to public oratory, diplomacy, media engagement, and Islamic preaching, this research highlights how his methods remain relevant in contemporary communication models. The study compares Prophetic communication with modern public speaking, corporate communication, diplomatic strategies, and media ethics, demonstrating the superiority of truth, wisdom, and sincerity in effective messaging. Additionally, the research emphasizes the importance of applying these principles in modern contexts such as countering Islamophobia, promoting ethical journalism, enhancing diplomatic relations, and utilizing digital platforms for Islamic outreach. By integrating Prophetic communication strategies into contemporary media and diplomatic frameworks, Muslim societies can establish a more truthful and impactful global narrative. The study concludes that the Seerah provides a timeless communication model, urging further research on its practical applications in today's digital and globalized world.